Formulation and Characterization of Tegoprazan Loaded Gastroretentive Microballoons - Rathore, Kavita; Singh Rajput, Dharmendra; Gupta, Naveen (International Journal of Aquatic Research and Environmental Studies, 2026)
aTegoprazan is a novel potassium-competitive acid blocker (P-CAB) used in the management of gastric acid related disorders, including peptic ulcers and gastroesophageal reflux disease. However, maintaining prolonged gastric residence is essential to maximize its local therapeutic effect and improve treatment outcomes. The present study aims to formulate and characterize tegoprazan-loaded gastroretentive microballoons to enhance gastric retention, sustain drug release, and improve antiulcer activity. The microballoons were prepared using the solvent evaporation technique with suitable polymers, such as ethyl cellulose and hydroxypropyl methylcellulose (HPMC), to obtain hollow, low-density particles capable of floating in gastric fluid. The prepared formulations were evaluated for particle size, percentage yield, drug entrapment efficiency, buoyancy, surface morphology, in vitro drug release, and compatibility using analytical techniques including Fourier Transform Infrared Spectroscopy (FTIR). The optimized formulation exhibited high entrapment efficiency, excellent floating ability for more than 12 hours, and sustained drug release following controlled-release kinetics. The prolonged gastric residence and controlled drug release are expected to enhance the bioavailability and antiulcer efficacy of tegoprazan while reducing dosing frequency and improving patient compliance. These findings suggest that gastroretentive microballoons represent a promising oral drug delivery system for optimizing the therapeutic performance of tegoprazan in the treatment of gastric ulcers and other acid-related disorders.
Keywords: Tegoprazan, Pharmacokinetics, antiulcer activity, bioavailability, controlled-release kinetics, microballoons , gastric ulcers